Remote impact of the Antarctic atmosphere on the southern mid-latitudes - Tido Semmler; Marta A. Kasper; Thomas Jung; Soumia Serrar (Meteorologische Zeitschrift, 2016)
Would improved prediction capabilities over the Antarctic lead to improved forecast skill in southern mid-latitudes? Or more generally speaking, how large is the influence of the Antarctic atmosphere on the weather and climate of the southern mid-latitudes? To answer these questions we assess the skill of two sets of 14‑day forecasts with the Integrated Forecast System of the European Centre for Medium-Range Weather Forecasts with and without relaxation towards the Interim reanalysis of the ECMWF over the Antarctic south of 75 ° S. Due to the relaxation both the mean absolute error and the root mean square error decrease by 2 to 5 % averaged over the southern mid-latitudes with the larger values in winter. Over southern South America and the South Atlantic error reductions are slightly larger and amount to around 5 to 6 %. No dependency of the error reductions of the El Niño Southern Oscillation or the Antarctic Oscillation could be found although error reductions averaged over the whole southern mid-latitudes tend to be larger in situations with decreased westerly flow in the mid-latitudes. In weather situations with anomalous meridional flow from Antarctica to southern South America improvements are most pronounced in the latter area which implies that this is the major pathway for Antarctic influence on southern mid-latitude weather and climate.